Binding constant determination of uranyl–citrate complex by ACE using a multi‐injection method. Issue 7 (23rd March 2015) - Zhang, Yiding; Li, Linnan; Huang, Hexiang; Xu, Linnan; Li, Ze; Bai, Yu; Liu, Huwei
Abstract : The binding constant determination of uranyl with small‐molecule ligands such as citric acid could provide fundamental knowledge for a better understanding of the study of uranyl complexation, which is of considerable importance for multiple purposes. In this work, the binding constant of uranyl–citrate complex was determined by ACE. Besides the common single‐injection method, a multi‐injection method to measure the electrophoretic mobility was also applied. The BGEs used contained HClO4 and NaClO4, with a pH of 1.98 ± 0.02 and ionic strength of 0.050 mol/L, then citric acid was added to reach different concentrations. The electrophoretic mobilities of the uranyl–citrate complex measured by both of the two methods were consistent, and then the binding constant was calculated by nonlinear fitting assuming that the reaction had a 1:1 stoichiometry and the complex was [(UO2 )(Cit)] − . The binding constant obtained by the multi‐injection method was log K = 9.68 ± 0.07, and that obtained by the single‐injection method was log K = 9.73 ± 0.02. The results provided additional knowledge of the uranyl–citrate system, and they demonstrated that compared with other methods, ACE using the multi‐injection method could be an efficient, fast, and simple way to determine electrophoretic mobilities and to calculate binding constants.